Association Between Very Low Levels of High‐Density Lipoprotein Cholesterol and Long‐term Outcomes of Patients With Acute Coronary Syndrome Treated Without Revascularization: Insights From the TRILOGY ACS Trial. Issue 6 (13th May 2016) - Hagström, Emil; Roe, Matthew T.; Hafley, Gail; Neely, Megan L.; Sidhu, Mandeep S.; Winters, Kenneth J.; Prabhakaran, Dorairaj; White, Harvey D.; Armstrong, Paul W.; Fox, Keith A.A.; Ohman, E. Magnus; Boden, William E.; et al.
ABSTRACT: Background: Low levels of high‐density lipoprotein cholesterol (HDL‐C; <40 mg/dL) are associated with increased risk of cardiovascular events, but it is unclear whether lower thresholds (<30 mg/dL) are associated with increased hazard. Hypothesis: Very low levels of HDL‐C may provide prognostic information in acute coronary syndrome (ACS) patients treated medically without revascularization. Methods: We examined data from 9064/9326 ACS patients enrolled in the TRILOGY ACS trial. Participants were randomized to clopidogrel or prasugrel plus aspirin. Study treatments continued for 6 to 30 months. Relationships between baseline HDL‐C and the composite of cardiovascular death, myocardial infarction (MI), or stroke, and individual endpoints of death (cardiovascular and all‐cause), MI, and stroke, adjusted for baseline characteristics through 30 months, were analyzed. The HDL‐C was evaluated as a dichotomous variable—very low (<30 mg/dL) vs higher (≥30 mg/dL)—and continuously. Results: Median baseline HDL‐C was 42 mg/dL (interquartile range, 34–49 mg/dL) with little variation over time. Frequency of the composite endpoint was similar for very low vs higher baseline HDL‐C, with no risk difference between groups (hazard ratio [HR]: 1.13, 95% confidence interval [CI]: 0.95‐1.34). Similar findings were seen for MI and stroke. However, risks for cardiovascular (HR: 1.42, 95% CI: 1.13‐1.78) and all‐cause death (HR: 1.36, 95% CI: 1.11‐1.67) were higher in patients with very low baseline HDL‐C. Conclusions: Medically managed ACS patients with very low baseline HDL‐C levels have higher risk of long‐term cardiovascular and all‐cause death but similar risks for nonfatal ischemic outcomes vs patients with higher baseline HDL‐C.